(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2015)
Emulsifier used in the preparation of chocolate has the function to stabilize fat and water that can prevent the occurrence of blooming. Emulsifier generally used in the preparation of chocolate is lecithin. However as an alternative monodiacylglycerol (MDAG) can be used. MDAG can be synthesized from vegetable oil such as palm oil and its fraction. This research was conducted to study the effect of palm MDAG and variation of its concentration on quality of chocolate. The palm MDAG used was palm kernel oil MDAG (MDAG PKO), palm olein MDAG (MDAG POL), palm stearin MDAG (MDAG PS) at the concentration between 0.3 to 0.9%. Results of the study showed that chocolate which used palm MDAG did not cause blooming. Increase of MDAG concentration tended to increase fat content but the reverse result was observed in the case of lecithin. The melting point of chocolate tended to increase with increasing concentration of MDAG POL and MDAG PS but the reverse result was observed in lecithin, meanwhile for MDAG PKO similar result was observed. The protein content of chocolate tended to decrease with increasing MDAG concentration but the reverseresult was observed in lecithin. Viscosity of chocolate with lecithin, MDAG PKO and MDAG POL decreased in accordance with increasing concentration, meanwhile in MDAG PS at the concentration of 0.3% in the beginning viscosity decreasedbut later on increased with increasing concentration. The use of emulsifier at the concentration of 0.3–0.9% did not have significant effect on fat content, melting point of fat and protein content, but it had significant effect on viscosity. Results of organoleptic testing showed that the use of palm MDAG have not significant effect on texture, taste, and appearance of chocolate. Types and concentrations of palm MDAG which were highly accepted by the panelist there were MDAG PS and MDAG PKO with concentration 0.3% and 0.5%, respectively. Keywords: chocolate, cocoa butter substitute, lecithin, palm oil, palm kernel oil